A Complete Quantitative Analysis of Spatio‐Temporal Dynamics of Excitons in Functional Organic Light‐Emitting Diodes. Issue 2 (14th October 2016) - Dey, Amrita; Rao, Akshay; Kabra, Dinesh
Abstract : The spatio‐temporal dynamics of excitons in functional polymer light‐emitting diodes reveal that singlet–triplet annihilation (STA) is significantly higher than the often invoked singlet–polaron annihilation (SPA). STA holds back the efficiencies of PLEDs and further realization of organic injection lasers. Additional singlets are found in F8BT that are related to thermally activated delayed fluorescence (TADF), as triplet–triplet annihilation (TTA) alone cannot account for the observed high external quantum efficiencies.